"…they think we are conversing, so we don't care about them…" Examining the causes of workplace violence against nurses in Ghana. Issue 1 (December 2016) - Boafo, Isaac
Abstract Background This study is part of a larger project aimed at exploring the workplace experiences of nurses working in public general hospitals in Ghana. The current paper explores the causes of workplace violence against nurses in Ghana. Methods Twenty-four semi-structured in-depth interviews were conducted with professional nurses working in five regions of Ghana. They were selected through purposive and participant-to-participant snowball sampling techniques. Data was analysed through thematic analyses. Results The findings of the study suggest that nurses are not (always) passive recipients of violence. Workplace violence can be instigated by either of the parties to the nurse-patient/relative interaction. Nurses' accounts of the causes of violence suggest that violence could be instrumental or reactive. The study further suggests that the causes of violence may differ depending on which party instigated the violence. The main causes of violence identified include ineffective communication, long waiting times and perceived unresponsiveness, and enforcement of visiting hours. Conclusion It is concluded that workplace violence could be reduced through the provision of adequate information to patients and their relatives. Nurses could also be trained in effective communication and interpersonal skills; and on how to identify and avoid potentially violent situations. It is also imperative that policies and measures aimed at addressing workplace violence are instituted to address the problem. Mass education may also be carried out to sensitise the general public on the adverse effects of violence against nurses.